1996
DOI: 10.1002/(sici)1096-8652(199601)51:1<26::aid-ajh5>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective discharge of patients with acute myeloid leukemia during chemotherapy-induced neutropenia

Abstract: Purpose. it is common practice for patients with acute myeloid leukemia (AML) to be observed in hospital during the entire nadir after intensive chemotherapy. in an attempt to lessen the likelihood of developing infections with hospital acquired pathogens, we usually discharge patients upon completion of chemotherapy and follow them as outpatients. They are readmitted if fever develops. We evaluated the feasibility and safety of this practice. Patients and Methods. We studied 29 patients with AML (median age 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…Another study evaluating outpatient versus inpatient AML intensification chemotherapy found fewer days of febrile neutropenia and less antimicrobial use among outpatients than children receiving inpatient treatment . Likewise, previous evaluations among adult AML patients found outpatient supportive care to be associated with fewer and shorter febrile episodes and fewer days of intravenous antibiotic administration . The findings with respect to antimicrobial agent use contradict those of the current study.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Another study evaluating outpatient versus inpatient AML intensification chemotherapy found fewer days of febrile neutropenia and less antimicrobial use among outpatients than children receiving inpatient treatment . Likewise, previous evaluations among adult AML patients found outpatient supportive care to be associated with fewer and shorter febrile episodes and fewer days of intravenous antibiotic administration . The findings with respect to antimicrobial agent use contradict those of the current study.…”
Section: Discussioncontrasting
confidence: 97%
“…However, a recent survey of pediatric supportive care practices suggests that up to one‐third of pediatric AML patients are discharged early to outpatient management during postchemotherapy neutropenia . While outpatient supportive care in this population has only been examined in a single study of 26 patients , several studies of adult AML patient populations suggest that outpatient management during neutropenia may be safe and feasible . Early hospital discharge was associated with fewer febrile episodes , reduced use of intravenous antibiotics and comparable mortality .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Furthermore, several studies (including 2 at our institution) have shown that early discharge after intensive induction chemotherapy is feasible, safe, and reduces daily charges in selected patients. [14][15][16][17] In contrast, no studies, to the best of our knowledge, have thus far investigated outpatient administration of intensive induction chemotherapy in patients with AML and high-risk MDS. This prompted conduct of the current pilot study to test the feasibility of outpatient intensive induction chemotherapy for select patients with AML and high-risk MDS and to preliminarily assess its impact on resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…These infections require intravenous broad‐spectrum antibiotics 1, 4, 6, 10, as well as antibiotic prophylaxis (AP) during neutropenia, which has been shown to improve infection prevention and overall survival 2. Non‐randomized studies show that treatment of acute leukemia can be performed on an outpatient basis, allowing the patient to remain at home while under supervision in the active treatment phase and neutropenia period 11, 12, 13, 14, 15, 16, 17, 18, 19. Though feasible and safe, findings from our outpatient management study for acute leukemia showed that neutropenic fever followed by septicemia and pneumonia are the dominant causes of readmission during outpatient management 20.…”
Section: Introductionmentioning
confidence: 99%